2017
DOI: 10.2139/ssrn.2911460
|View full text |Cite
|
Sign up to set email alerts
|

Crime and the Legalization of Recreational Marijuana

Abstract: First-pass evidence is provided that the legalization of the cannabis market across US states is inducing a crime drop. We exploit the staggered legalization of recreational marijuana enacted by the adjacent states of Washington (end of 2012) and Oregon (end of 2014). Combining county-level difference-in-differences and spatial regression discontinuity designs, we find that the policy caused a significant reduction in rapes and property crimes on the Washington side of the border in 2013-2014 relative to the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
1
30
0
2
Order By: Relevance
“…Road fatalities in fact may continue to occur after the enactment of the MUP reform if drivers substitute away from alcoholic beverages to other driving-impairing substances, such as illegal drugs. If such a substitutability were at work as suggested by several empirical studies (e.g., DiNardo and Lemieux, 2001;Crost and Guerrero, 2012;Anderson et al, 2013;Dragone et al, 2019), a reduction in Q would not lead to a reduction in E, because ρ is close to zero. This implies π 1 would be close to zero as well.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…Road fatalities in fact may continue to occur after the enactment of the MUP reform if drivers substitute away from alcoholic beverages to other driving-impairing substances, such as illegal drugs. If such a substitutability were at work as suggested by several empirical studies (e.g., DiNardo and Lemieux, 2001;Crost and Guerrero, 2012;Anderson et al, 2013;Dragone et al, 2019), a reduction in Q would not lead to a reduction in E, because ρ is close to zero. This implies π 1 would be close to zero as well.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…There is also evidence that marijuana substitutes for alcohol and that, in states that legalize marijuana, alcohol consumption decreases (Anderson et al., 2013; Dragone et al., 2019). Furthermore, the AFCARS data do report removals for parental alcohol abuse separately from other forms of parental drug use, enabling us to provide some direct evidence on the relative importance of substitution effects.…”
Section: Empirical Evidencementioning
confidence: 99%
“…These legalizations represent a radical departure from long‐standing policy toward the drug, and have attracted commensurate attention from researchers. While much of the literature on legalization has centered on its effects on broader socioeconomic outcomes such as housing prices and crime (see, e.g., Brinkman & Mok‐Lamme, 2019; Cheng et al., 2018; Dragone et al., 2019), less is known about the direct welfare consequences of legalization policies for marijuana users and those close to them. Less still is known about the effects of legalization on child welfare.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies related to opioid overdoses and medical legalization show that there may not be a correlation as previously suggested [23]. A modest reduction in violent crimes has also been observed following recreational marijuana legalization [24]. Conversely, studies have shown a temporary increase in traffic fatalities following recreational marijuana legalization in US and neighboring jurisdictions [25].…”
Section: Introductionmentioning
confidence: 99%